Prevalence of obesity using new adiposity indices among the Barwar community: A Denotified Tribe of Gonda district, Uttar Pradesh, India - Biswajit Mahapatra (Elsevier, 2023)
Introduction: The present study assesses the prevalence of obesity using new adiposity indices and evaluatesthe association between socio-demographic factors and combined obesity among the denotified tribe of Gonda district, Uttar Pradesh, India. Materials and methods: The present study was undertaken among 315 rural adults (141 males; 174 females) aged 20-59 years. Sex wise mean differences were observed by the t-test. The Chi-square tests were used for any significant relationships between categoricalvariables. Binary logistic regression was used to identify the risk factors for combined obesity. ROC curve was used for predicting the combined obesity. Results: The prevalence's of combined general obesity, combined central obesity, and overall combined obesity are 34.9%, 69.8%, and 75.6% respectively. Combined obesity always shows higher prevalence of obesity than any obesity-related single parameter. The prevalence of single obesity, dual obesity, and no obesity is 46.3%, 29.3% and 24.4% respectively. In the case of all socio demographic parameters, widow shows the high risk of CGO (OR = 8.83, CI: 1.97-39.58, p= <0.01) and the higher age groups (50-59 years) show the higher risk of CCO (OR = 4.95, CI: 2.47-9.90, p= <0.001) and OCO (OR = 6.51, CI: 2.68-15.84, p= <0.001). Conclusion: The current study concludes that any single parameter or index is not enough to measure the actual prevalence of obesity. The present study shows females have a higher prevalence of all three types of combined obesity than males. Combined obesity assesses the overall magnitude of obesity and identifies communities with multiple obesity parameters.